Boundary friction characterisation of a used cylinder liner subject to fired engine conditions and surface deposition. (March 2019) - Bewsher, S.R.; Leighton, M.; Mohammadpour, M.; Rahnejat, H.; Offner, G.; Knaus, O.
Abstract: For future engines to become more efficient, with enhanced fuel economy and increased power output, accurate prediction of new designs is required over the full lifetime of an engine. The analysis uses of a local pressure coefficient of boundary shear strength of asperities value, taking into account the localised effects of surface texture, coating and surface deposition. XPS spectra analysis was also carried out to identify the surface depositions as a result of combustion, not previously taken into account during piston ring pack simulation. It was found that piston varnish on the liner corresponded to higher values of the pressure coefficient of boundary shear strength of asperities, showing the importance of using real system components run under representative operating conditions. Highlights: The paper presents measurements of ς from a used real cylinder liner surface. XPS is used to identify chemical composition of liner surface regions. Depositions and tribo-films on the liner surface are characterised. Results show that boundary friction is dependent on the by-products of combustion over time. Simulation shows that results for friction can vary by 30% at peak combustion pressure.